2020
DOI: 10.1080/10410236.2020.1847445
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Online Health Information Searching and Brokering: Framing Health Literacy as a Family Asset

Abstract: Latino populations are disproportionately impacted by health disparities and face both connectivity and health literacy challenges. As evidenced by the current global pandemic, access to reliable online healthrelated information and the ability to apply that information is critical to achieving health equity. Through a qualitative study on how Latino families collaborate to access online health resources, this work frames health literacy as a family-level mechanism. Interviews with parent-child dyads combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Much of these practices are habits as doctors often have little training in seeking information (Balicco and Pagenelli, 2011). Bilingual children of immigrants or racial minorities might conduct searches and seek information in English for their parents, serving as proxy information seekers (Gonzalez et al. , 2020).…”
Section: Information Practicesmentioning
confidence: 99%
“…Much of these practices are habits as doctors often have little training in seeking information (Balicco and Pagenelli, 2011). Bilingual children of immigrants or racial minorities might conduct searches and seek information in English for their parents, serving as proxy information seekers (Gonzalez et al. , 2020).…”
Section: Information Practicesmentioning
confidence: 99%
“…Conducting three separate visits also allowed us triangulation between the interviews and tasks. This study is situated in a larger investigation on immigrant Latin American families and their online search and brokering behaviors (Gonzalez et al , 2020; Pina et al , 2018; Roldan, 2021; Roldan et al , 2019). This paper provides a more focused analysis on the specifics of joint media engagement (Takeuchi and Stevens, 2011) as it pertains to family work.…”
Section: Methodsmentioning
confidence: 99%
“…In comparison to our other investigation on 24 families (Pina et al , 2018; Gonzalez et al , 2020), for this paper, we selected three focal families as case studies (Table 1). While not representative, these three focal families reflected patterns observed in other families (Pina et al , 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RenderX considerations for culture and language are a fertile area of future research examining reasons for the lack of OHI seeking (eg, learning styles and preferences, availability and access to Spanish-language computer resources, knowledge, and technological skills, such as search strategies, among others). In considering culture, previous studies exploring OHI behaviors suggested that younger, English-dominant Latino and Hispanic generations may be OHI brokers for older generations of SD Latino adults [4,35,60]. Therefore, whether OHI seeking could be facilitated by intergenerational co-learning approaches is an avenue for future exploration.…”
Section: Xsl • Fomentioning
confidence: 99%